Centennial Memorial March, 1776-1876 - Charles Grobe::::::::: (Mirsalis & Hamel)
Piano score, 8 p. At head of title: To Alfred T. Goshorn, Esq., Director-General of the Centennial Exhibition, Philadelphia. Cover lithograph signed, A. Bland?